INSTITUTIONAL REGULATION OF EXPORT ACTIVITIES OF INDUSTRIAL ENTERPRISES - SVYDRUK, IRENA; TURYANSKYY, YURIY (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to study the existing and outline promising areas for improving the institutional regulation of export activities of industrial enterprises of Ukraine. It is shown that the main purpose of the institutional mechanism of regulation of foreign economic activity of industrial enterprises is to create conditions for increasing its efficiency. The main tools of the institutional mechanism of foreign trade regulation are determined – tariff and non-tariff regulation, financial support through export credit and insurance systems, creation of an effective information support system. Analysis of the effectiveness of institutional regulation has shown significant potential for improvement. Despite the general reduction in foreign trade turnover in 2020 and the deterioration of the balance, the growth of export activity of Ukrainian producers in some countries was revealed. It is noted that under the Association Agreement with the EU there is a gradual abolition of import duties, but the issue of non-tariff regulation remains unresolved. It is shown that the establishment of the Export Promotion Office allowed to systematize the processes of institutional influence on the strategy of development of export-oriented sectors of the economy, analytical and legal support, improved access of domestic industrial enterprises to financing and business infrastructure. At the same time, in order to increase the efficiency of institutional regulation of foreign economic activity of industrial enterprises, it is expedient to intensify legislative activities, in particular on harmonization with EU legislation, standards and practices in such areas as technical barriers, customs, protection of intellectual property rights. Harmonization should be carried out taking into account the potential for export growth, involvement in international value chains and the tasks of export diversification in accordance with the Export Strategy of Ukraine. It is important to intensify institutional mechanisms for the protection of export-oriented foreign investment, to provide favorable macroeconomic conditions for financing industrial enterprises. Such direction of institutional regulation of foreign economic activity needs further development, is the provision of information and consulting support to domestic exporting companies in finding promising markets for products, partners in such markets, advising on how to penetrate foreign markets. The direction of further research may be the impact of digital transformations and digitalization of the domestic economic space on the possibility of improving the institutional regulation of foreign economic activity of Ukrainian enterprises.